Assessing the quality of care for knee osteoarthritis in Singapore: a cross-sectional study - Ren Hao Linus Tan; Anthony J. Goff; Chien Joo Lim; Yijia Bryan Tan (BMC Musculoskeletal Disorders)
Abstract Introduction The aim of this study was to assess the self-reported quality of care for people with knee osteoarthritis in Singapore and to investigate the associations between participant characteristics and functional outcomes at 1 year in relation to the reported quality of care. Methods Patients with knee osteoarthritis completed the osteoarthritis quality indicator (OA-QI) questionnaire, a validated patient-reported measure that assesses the clinician’s adherence to evidence-based guidelines for non-surgical knee osteoarthritis education and patient education. The OA-QI includes 17 indicators, with "achievement" defined as a 'Yes' response for each. We calculated individual per-item, overall per-item mean, and per-person achievement rates (%) and examined associations between participant characteristics, achievement rates, and function at 1 year. Results A total of 314 participants completed the OA-QI. Referral for physical activity (87.5%) and referral for daily activity aid assessment (15.7%) had the highest and lowest per-item achievement rates, respectively. The overall mean per-item and per-person achievement rates were both 62.2%. Participants educated about steroid injections (adjusted coefficient [95% CI]: 7.23 [1.42–13.04]; p = 0.015) or surgery (adjusted coefficient [95% CI]: 12.65 [5.89–19.40]; p < 0.001) had worse functional outcomes at one year than those who were eligible but not informed. Those not assessed for walking aids and indicating walking issues had poorer outcomes one year later (adjusted coefficient [95% CI]: -9.89 (-19.63, -0.15); p = 0.0470). However, no significant associations were found between per-person achievement rates and 1-year functional outcomes. Conclusions The quality of care in Singapore for people with knee osteoarthritis is suboptimal, especially for those needing walking aids and weight loss assistance. However, the quality of care alone does not fully account for long-term outcomes, suggesting that other factors need to be considered.